Pengaruh Peluang Usaha, Lingkungan Keluarga dan Motivasi Diri Terhadap Minat Berwirausaha Syariah Masyarakat Desa Purworejo, Kecamatan Bae, Kabupaten Kudus - Anggita Wahyu Fitriana; Tuti Nadhifah; Muhammad Nur Salim (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of business opportunities, family environment, and self-motivation on the interest in Islamic entrepreneurship among the people of Purworejo Village, Bae District, Kudus Regency. The research method used is mixed methods, which is a method that combines quantitative and qualitative approaches supported by interview results. The study population was the people of Purworejo Village who have entrepreneurial abilities, with a total of 89 respondents selected through a purposive sampling method. Data were collected using questionnaires and in-depth interviews. Data analysis was carried out using multiple linear regression methods, with SPSS software being used for the process. The results of the study indicate that business opportunities do not significantly influence interest in Sharia entrepreneurship, while family environment and self-motivation have a significant partial influence. Simultaneously, the three independent variables significantly influence interest in Sharia entrepreneurship with a coefficient of determination of 0.495. This indicates that 49.5% of interest in Sharia entrepreneurship is influenced by business opportunities, family environment, and self-motivation, while the remaining percentage is influenced by other factors not covered in this study. Qualitative findings reinforce that support from family and enthusiasm within a person are the main factors that encourage people to choose to become entrepreneurs based on Sharia principles.